Evaluation of the extension activities of the National Livestock Projects Division Kontagora, Nigeria (2003)
An evaluation study of five commodity-based livestock extension models of the Kontagora district officer of the National Livestock Project Division (NLPD) under Nigeria’s Second Livestock Development Plan (NLDP) was carried out between 1992 and 1996. The adoption rates for the models were 27.8% for the Small Holder Cattle Fattening Scheme (SHCFS). 16.3% for the poultry model and 14% for the piggery model. All the adopters of the SHCFS received virtually all their inputs at subsidised rates through the NI, PD. In contrast, virtually no extension service or inputs were provided to the poultry and pincers models, hence the lower adoption rates, despite strong evidences of socio-economic relevance. The correction of the extension delivery detects indicated, and a major policy reorientation towards the development of poultry and pigs hand-in-hand with cattle to alleviate Nigeria’s animal protein deficit, are recommended.